2009
DOI: 10.1007/s12272-009-1300-4
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide and multisulfide antitumor agents and their modes of action

Abstract: A variety of natural products that contain disulfide or multisulfide bonds were found to display potent biological activities, including antitumor activities. At the center of these biological activities are disulfide or multisulfide moieties. The importance of disulfide or multisulfide groups in the areas of chemistry, biology, and pharmacology has been well recognized. Among these agents, especially noteworthy are mitomycin disulfides, leinamycin, thiarubrines, varacins, calicheamicins, and esperamicins. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 121 publications
0
21
0
Order By: Relevance
“…Disulfide bonds are covalent bonds that form via the oxidation of two sulfhydryl (SH) residues of cysteines or other substances. Disulfide bonds have already been discovered in proteins as well as multiple natural products, including therapeutic drugs . They play an important role in the folding of proteins and enhancing protein stability because they can reduce the entropy of the denatured state .…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide bonds are covalent bonds that form via the oxidation of two sulfhydryl (SH) residues of cysteines or other substances. Disulfide bonds have already been discovered in proteins as well as multiple natural products, including therapeutic drugs . They play an important role in the folding of proteins and enhancing protein stability because they can reduce the entropy of the denatured state .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Owing to the increasing importance of the disulfides (disulfanes) in chemistry [9][10][11][12][13][14] and biology, [15][16][17] synthetic approaches for their preparation have been extensively studied. [18][19][20][21][22] According to the literature, disulfides can be obtained directly from *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic (Allium sativum) has been used in medicines and foodstuff for almost three thousand years as evidenced by ancient writings from China, Egypt, Greece, and India [1,2]. Epidemiological studies have shown that the enhanced dietary intake of garlic could reduce the incidence of various types of tumors such as colon, breast, lung, prostate, and stomach [3][4][5][6][7][8][9]. Garlic gives other beneficial effects including anti-atherosclerosis [10], blood lipids and sugar modulation [11], antifungal [12], antimicrobial [13], antithrombotic [14], cardiovascular disease treatment [15] and stimulating immune system [16].…”
Section: Introductionmentioning
confidence: 99%